Nature and Origin of a Massive Sulfide Occurrence in the Karrat Group: Evidence for Paleoproterozoic VMS Mineralization in Central West Greenland - DeWolfe, Y. M.; Kolb, J.; Sorensen, E. V.; Rosa, D.; Guarnieri, P. (Society of Economic Geologists, 2024)
Mafic volcanic rocks of the Kangilleq Formation of the Paleoproterozoic Karrat Group host volcanogenic massive sulfide (VMS) mineralization in the area of central Kangiusap Kuua, central West Greenland. The mafic volcanic rocks display evidence of subaqueous, effusive eruption and redeposition by mass debris flows generated along fault scarps on the sea floor. A zone of semiconformable quartz alteration and disconformable chlorite alteration within hydrothermal breccias and mafic tuff breccias near the top of the volcanic sequence is interpreted to reflect a synvolcanic hydrothermal system. Conformable, massive to semimassive, and discordant, stringer-style sulfide mineralization is hosted within the quartz- and chlorite-altered volcanic rocks. The massive to semimassive sulfide mineralization is ~10 m thick and crops out along strike for ~2,000 m. The stringer zone is ≤10 m thick with individual sulfide stringers ranging in width from 5 to 90 cm. All sulfide zones are dominated by coarse pyrrhotite and pyrite, with trace amounts of sphalerite and chalcopyrite. The pillow lavas are subalkaline with geochemical characteristics typical of modern transitional to tholeiitic mid-ocean ridge or back-arc basin basalt. Trace element and Nd isotope data suggest that these lavas erupted in an epicratonic, back-arc basin. Characteristics of the host rocks indicate a period of localized rifting, volcanism, and VMS formation during genesis of the Karrat Group, which is dominated by siliciclastic rocks.